Elaboración de un sistema de gestión de calidad para la carrera de Ingeniería Industrial de la Universidad Técnica de Cotopaxi. - Sigcho Lala, Christian Darío (2020)
The Industrial Engineering Major belongs to the Technical University of Cotopaxi located at Cotopaxi province, training quality professionals for society over 25 years, one of the most common problems that can be identified is the lack of documentation that allows to identify the substantive processes that make up the Major, currently there is a planning with which the activities are carried out, however the documentation and formats of each process is not documented or subject to revisions for improvement or editing. The Industrial Major has four substantive processes Academic Management, Teaching, Research and Linkage with the Society, which are the main object of this research in determining its corresponding activities and formats, research-style methodology, which helps establish the processes that take place within the Major. Due to the recent increase in interest in quality in all organizations, there is a need to offer products and services with a high quality degree that is perceived by users who over time have more demands and must be ensured that products or services meet the users needs and requirements, for this reason this research has as its main objective the Quality Management System development under the ISO 9001:2015 approach, obtaining as results the design of the Quality Management System, definition, characterization of the substantive processes of Industria's Major, formats that make up them and corresponding indicators. This research sets out in summary the proposal for the Quality Management System (SGC) to the Industrial Major at Technical University of Cotopaxi, since it contains the necessary documentation regarding each substantive process, the same as can be monitored and controlled through internal auditing and follow-up activities, providing continuous and organizational improvement.